Effectiveness of potassium humate and endophytic bacteria from Serratia marcescens strain NPKC3_2_21 in increasing root weight of paddy cultivation in acidic soil - GUNAWAN SUTIO; ISKANDAR ISKANDAR; LILIK T. INDRIYATI; GUNAWAN DJAJAKIRANA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sutio G, Iskandar, Indriyati LT, Djajakirana G. 2023. Effectiveness of potassium humate and endophytic bacteria from Serratia marcescens strain NPKC3_2_21 in increasing root weight of paddy cultivation in acidic soil. Biodiversitas 24: 6316-6322. Phosphorus (P) deficiency is a significant factor limiting rice agricultural production in acidic soil. The availability of P in acidic soil is generally insufficient because a substantial portion of P is absorbed by Al³? and Fe²?, rendering it inaccessible to plants. This P deficiency in acidic soil hampers proper root growth. However, this limitation can be overcome by the application of potassium humate and endophytic bacteria. The objective of this study was to investigate the effects of phosphate fertilizer with and without potassium humate and/or endophytic bacteria on root growth in acidic fields. The research involved two treatment factors. The first factor comprised four levels of ex-madura phosphate rock fertilizer: 100% (1), 75% (2), 50% (3), 25% (4), and no application of phosphate rock fertilizer (5) and the second factor included potassium humate (A), endophytic bacteria from Serratia marcescens strain NPKC3_2_21 (B), a combination of potassium humate and S. marcescens endophytic bacteria (C), and the absence of both potassium humate and S. marcescens endophytic bacteria (D). The results revealed a positive interaction between phosphate fertilizer, the combination of potassium humate, and S. marcescens endophytic bacteria. Therefore, utilizing endophytic bacteria from S. marcescens and potassium humate could be an effective strategy for increasing root biomass in rice plants grown in acidic soil with a deficiency in available P.